Short‐range ordering in the Li‐rich disordered rock salt cathode material Li2VO2F revealed by Raman spectroscopy. (24th July 2020) - Mozhzhukhina, Nataliia; Kullgren, Jolla; Baur, Christian; Gustafsson, Olof; Brant, William R.; Fichtner, Maximilian; Brandell, Daniel
Abstract: Li‐rich disordered rock salt (DRS) materials are new promising high‐capacity cathode candidates for Li‐ion batteries. DRS structures were initially assumed to have a completely random cation and anion distribution, but recent reports suggest that some of these structures can exhibit local atomic arrangements, or short‐range ordering (SRO). Here, we prove the existence of SRO in the Li‐rich DRS material Li2 VO2 F by employing Raman spectroscopy supported by density functional theory (DFT) calculations. Our results suggest that this combination of Raman spectroscopy with computational tools is useful for SRO estimation in this new class of Li‐rich DRS cathode materials. Abstract : Local structural symmetries in disordered rock salt oxyfluoride Li2 VO2 F were studied by Raman spectroscopy supplemented by computations using DFT. The material possesses very specific short‐range order that is hidden in the corresponding conventionally analyzed diffraction patterns. These results display that Raman spectroscopy in combination with DFT calculations is a powerful tool in order to characterize ionic short‐range order arrangements and thereby to estimate the anion redox reactions in Li‐rich disordered rock salt materials.